(untitled) (African Journal of Biomedical Research, 2020)
All women deserve humane, considerate, sensitive and respectful care in childbirth. Respectful maternity care (RMC) is human right and standard midwifery practice. However there have been general public complaints about lack of respectful behaviour by midwives. To determine clients’ experience of respectful maternity care and midwives’ caring behaviour, two hospitals in Calabar, Nigeria were selected for this study. This descriptive study collected data from 83 purposively selected postnatal women who had spontaneous vaginal delivery, and 51 midwives caring for them. Ethical clearance was obtained from the HREC of Cross River State Ministry of Health and informed consent from participants. Clients and midwives identified respectful maternity care received/practiced from the RMC checklist. Data were analyzed using SPSS version18.0. RMC was reported by 58 (69.9%) clients while 25 (30.1%) reported lack of it in different categories. Non-respectful care reported included lack of privacy, lack of information about progress of labour, denying preference and choice of childbirth position, lack of sensitivity towards clients’ pain and culture, verbal abuse, detention in facility for non-payment of bill. Attending midwives confirmed not adequately screening or draping women (because of lack of screens and drapes); restricting women to deliver in the dorsal position and detaining women if they cannot pay the bill (because of hospital policy). Common acts of disrespectful care experienced by women in this study fit into some of the categories identified in literature. Appropriate maternity care must be respectful and rights-based in order to enhance utilization of maternity services and access to skilled care